Language, writing and literary communication: introductory notes - Ballón Aguirre, Enrique (1987)
How can we organize the literary production of the multi-lingual and pluricultural peruvian society? Through a brief introductory study of the materials, formal and functionals categories, that show the different literary discourses produced in Peru, the author propose an hipothesis about the characteristics that, in first instance, allow to classify this cultural production. In this article the author designs some criteria which provides an overview of the literary variables of the peruvian society.